An Application of Financial IT Programs to Support Customer Relations - Kubacka, Maria (Wykorzystanie finansowych programów informatycznych w zakresie wspierania relacji z klientami, 2022)
The aim of the paper was to present research on the status for the use of financial information systems and CRM systems or ERP modules for customer relationship management to support customer relations, and in particular to identify the status of the use of these systems depending on the type of an enterprise in the Podkarpackie province (voivodeship). At the same time, the study examined whether the customer relationship management system was coupled with the enterprise’s financial and accounting system in terms of importing customer information, and the sources of obtaining customer information were identified. On the basis of the research conducted, it should be stated that the CRM class system was functioning in almost 31% of the enterprises under the survey. As a result of the analysis of contingency tables and verification of statistical significance of the relationships studied, and using the chi-square independence test, it was confirmed that the type of enterprise differentiated the entities in terms of the use of CRM systems (or the relevant ERP modules for customer relationship management) in supporting customer relations. At the same time, the study showed that the use of customer relationship management systems was related to the indication of the desired sources of customer information. The research filled a gap in knowledge about the use of customer relationship management systems in enterprises in the Podkarpackie province.
Financial Sciences. Nauki o Finansach, 2022, vol. 27, no. 2, s. 12-24
Keywords: accounting and financial systems; CRM; customer relations; system księgowo-finansowy; relacje z klientami